A Case of Violent Suicide Attempt in a Context of Myxedema Psychosis following Radioiodine Treatment in a Patient with Graves’ Disease - Louise Todorov; Amel Ait Boudaoud; Rachel Pascal de Raykeer; Alina Radu; Khadija Lahlou-Laforêt; Frédéric Limosin; Cédric Lemogne; Sébastien Czernichow (Case Reports in Psychiatry)
Introduction. Hypothyroidism has been associated with mood disorders but some cases of acute psychosis have also been reported. However, less attention has been paid to suicidal behavior in these patients. Case Report. We report a case of suicide attempt by self-stabbing in a 43-year-old woman without past psychiatric history, four months after radioiodine therapy for Graves’ disease. On clinical examination remarkable signs of myxedema were found and blood investigations showed hypothyroidism with an extremely high thyroid stimulating hormone (TSH) level (152 mUI/L; reference range 0.20-5.10). The patient presented delirium symptoms at the time of self-stabbing, which was associated with persecutory delusions and auditory harm command hallucinations. A rapid physical and psychiatric improvement was observed after the initiation of an oral thyroid replacement therapy without relapse after early discontinuation of the antipsychotic treatment. Discussion. The most distinctive feature of our case is that the violent suicide attempt could be attributed to the myxedema psychosis. Suicide may result from several factors, including psychosocial stressors, psychiatric symptoms, and hormonal disturbance. This unique presentation should remind clinicians to systematically consider ordering additional tests in patients with atypical psychiatric presentation, even when serious behavioral disorders (such as violent suicide attempts) are present and may result in premature transfer to psychiatric units.